Advances in accounting education : teaching and curriculum innovations - Calderon, Thomas G. (Emerald Publishing Limited, 2023)
Advances in Accounting Education: Teaching and Curriculum Innovations publishes both non-empirical and empirical articles dealing with accounting education. All articles emphasize teaching, learning and curriculum development, and discuss vital matters pertaining to the improvement of accounting programs at colleges and universities. Non-empirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate. This 27th volume features 11 peer-reviewed papers surrounding three themes: (1) applied professional research and skills building; (2) generative artificial intelligence (AI) and analytics in the accounting curriculum; and (3) innovative practices in cost accounting and other areas. Faculty with an interest in accounting education as well as accounting program administrators should find all three themes to be highly informative and interesting. Some practitioners and regulators in the accounting profession may also find useful policy-related nuggets in Volume 27.
Includes index.
Keywords: Accounting -- Education.; Accounting -- Study and teaching.; Education -- Finance.; Accounting.; elektronické knihy; electronic books